Exploring the psychological mechanisms of library anxiety considering achievement motivation and goal orientation - Masaki Takeda; Satoru Suto (Information Research: An International Electronic Journal, 2025)
Introduction. Although library anxiety is recognised as having a negative impact on people's exploration, its mechanisms are unknown. Moreover, no studies have systematically demonstrated the mechanisms through which exploration is modified in the context of library anxiety. This study reviewed the context and results related to library anxiety and hypothesised that achievement motives and goal orientations underlie changes in exploration.